Design of Broadband Compact Canonical Triple-Sleeve Antenna Operating in UHF Band - Chandana SaiRam; Damera Vakula; Mada Chakravarthy (Journal of Electromagnetic Engineering and Science, 2021)
In this paper, a novel compact broadband antenna at UHF frequencies is presented with canonical shapes. Hemispherical, conical and cylindrical shapes have all been considered for antenna configuration. The designed antenna provides an instantaneous frequency range from 370 to 5,000 MHz with omnidirectional characteristics. The antenna was simulated in CST Microwave Studio, fabricated and evaluated; the results are presented. The simulated and measurement results are in good agreement. The antenna has voltage standing wave ratio (VSWR) ≤ 1.9:1 in 400–570 MHz, 2,530–3,740 MHz and 4,180–4,620 MHz; it has VSWR ≤ 3:1 over the operating frequency range 370–5,000 MHz and the measured gain varies from −0.6 to 4.5 dBi over the frequency band. The concept of canonical-shaped antenna elements and the incorporation of triple sleeves resulted in a reduction of the length of the antenna by 62% compared to the length of a half-wave dipole antenna designed at the lowest frequency. The antenna can be used for trans-receiving applications in wireless communication.